2022
DOI: 10.1172/jci157340
|View full text |Cite
|
Sign up to set email alerts
|

The microbiome restrains melanoma bone growth by promoting intestinal NK and Th1 cell homing to bone

Abstract: Bone metastases are frequent complications of malignant melanoma leading to reduced quality of life and significant morbidity. Regulation of immune cells by the gut microbiome influences cancer progression, but the role of the microbiome in tumor growth in bone is unknown. Using intracardiac or intratibial injections of B16-F10 melanoma cells into mice, we showed that gut microbiome depletion by broad-spectrum antibiotics accelerated intraosseous tumor growth and osteolysis. Microbiome depletion blunted melano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 79 publications
0
29
2
1
Order By: Relevance
“…Our data further suggest that cells arrested very quickly after injection, within the first minute, likely through passive trapping in capillary beds. Interestingly, prior studies of metastases formation following intracardiac injection mainly reported bone metastases, 24,27,28 even though the musculoskeletal system accounted for only 22% of the cell arrest in our study. This observation suggests that the bone marrow may provide a more supportive niche for the survival and rapid growth of metastatic lesions, as originally postulated in the “seed and soil” hypothesis.…”
Section: Discussioncontrasting
confidence: 61%
“…Our data further suggest that cells arrested very quickly after injection, within the first minute, likely through passive trapping in capillary beds. Interestingly, prior studies of metastases formation following intracardiac injection mainly reported bone metastases, 24,27,28 even though the musculoskeletal system accounted for only 22% of the cell arrest in our study. This observation suggests that the bone marrow may provide a more supportive niche for the survival and rapid growth of metastatic lesions, as originally postulated in the “seed and soil” hypothesis.…”
Section: Discussioncontrasting
confidence: 61%
“…It has been observed that the growth of melanoma cells in bone triggers the proliferation of intestinal NK and Th1 cells and their homing to tumour-bearing bone to inhibit melanoma bone metastasis. This trigger is microbially dependent, and it is weakened by microbiome depletion, thus increasing the progression of bone metastasis [ 208 ]. Similarly, Yin et al found that Fusobacterium nucleatum promotes CRC liver metastasis by increasing the accumulation of MDSCs and Tregs in the liver of a CRC mouse model and reducing the infiltration of NK cells to inhibit the immune niche of the liver [ 209 ].…”
Section: Crosstalk Between Nk Cells and The Tmementioning
confidence: 99%
“…NK cells are key ILCs mediating tumor immunosurveillance and elimination ( 79 ). The gut microbiota was reported to blunt melanoma bone growth ( 51 ). Gut microbiota depletion by broad-spectrum antibiotics (ATB) promoted intraosseous melanoma growth by blocking melanoma-induced expansion of intestinal NK cells and Th1 cells and their egress from the gut into the bone marrow of tumor-bearing bones.…”
Section: The Gut Microbiota and Innate Immunitymentioning
confidence: 99%